3D reconstruction of structural magnetic resonance neuroimaging based on computer aided detection. (30th April 2021) - Mabrouk, Mai S.; Afify, Heba M.; Marzouk, Samir Y.
Computer aided detection (CAD) has numerous achievements in medical image processing field which represents a communication. Despite the advance in the radiological diagnosis of neuroimaging, magnetic resonance imaging (MRI) has some restrictions related to human errors and incomplete interpretation of brain tumour regions. Also, MRI produces 2D images of the brain that are very difficult to handle different types of tumour. This study investigated CAD system using 3D image reconstruction of MR brain and tumour structures efficiently. In addition, the proposed system applied the fuzzy C-means (FCM) algorithm as image segmentation, and support vector machine (SVM) as image classification for tumour detection of MR brain images. The results confirmed that this 3D model supported the advanced view of human brain diseases. The accurate and quantitative research results are expected to enhance the healthcare technology.